STUDI IMPLEMENTASI STANDAR SISTEM MANAJEMEN LINGKUNGAN (ISO 14001:2004) DALAM PENGELOLAAN WISATA ALAM DI TAMAN NASIONAL BROMO TENGGER SEMERU (Studi Kasus Pelaksanaan Sertifikasi dalam Pengelolaan Wisata Alam) - Dian Iswandaru; Ambar Kusumandari; Chafid Fandeli (Program Studi Manajemen Hutan, Pascasarjana Universitas Pattimura, 2016)
High nature potency, strategic location, and accessible have made TNBTS as one of most visited national parks, thus the potency cause negative impact to the ecosystem. To anticipate, the Management of TNBTS has applied environment management system/EMS based on ISO 14001 : 2004. The study aimed to investigate the EMS applied by the management of TNBTS, implementation process of ISO 14001 : 2004, evaluate the phase and percent of EMS application on natural tourism management. Method used was descriptive explorative with frequent descriptive analysis and SWOT analysis. The result showed that the most inï€‚uencing factor in the EMS application in TNBTS was visitor aspect and facilities establishment. Implementation process of ISO 14001 : 2004 in TNBTS was started with EMS training by an external consultant, agreeing the certification scope, conducting early review, and identifying environmental impact aspect also the regulation. Then set the environmental policy, management, conduct inspection and review of the management. To support successfulness of the implementation of ISO 14001 : 2004, requires management and personal commitment. Compliance degree of the EMS implementation based on ISO 14001 : 2004 was 3.86 and 79.95% with the category of close to consistent. Result of SWOT analysis showed that the strategic position of TNBTS in applying EMS to manage their natural tourism was in quadrant/ cell 1 (1.18; 0.65). Therefore, the strategy that can be developed is growth strategy, with the strategy form increasing service to visitors, increasing management work in maintaining the EMS quality.